2020
DOI: 10.3390/fi13010008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Deep Convolutional Generative Adversarial Networks for Data Augmentation of Chest X-ray Images

Abstract: Medical image datasets are usually imbalanced due to the high costs of obtaining the data and time-consuming annotations. Training a deep neural network model on such datasets to accurately classify the medical condition does not yield the desired results as they often over-fit the majority class samples’ data. Data augmentation is often performed on the training data to address the issue by position augmentation techniques such as scaling, cropping, flipping, padding, rotation, translation, affine transformat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 25 publications
0
11
0
3
Order By: Relevance
“…They also discussed that data augmentation of liver lesion data could improve the performance of liver lesion medical image classification by using CNN. Kora Venu et al [22] proposed a generative modeling method that includes DCGAN to produce fake CXR images from an under-represented class from the Chest X-ray dataset (DCGAN). This method constructed artificial samples by keeping identical properties to the actual data.…”
Section: Related Workmentioning
confidence: 99%
“…They also discussed that data augmentation of liver lesion data could improve the performance of liver lesion medical image classification by using CNN. Kora Venu et al [22] proposed a generative modeling method that includes DCGAN to produce fake CXR images from an under-represented class from the Chest X-ray dataset (DCGAN). This method constructed artificial samples by keeping identical properties to the actual data.…”
Section: Related Workmentioning
confidence: 99%
“…GAN can generate artificial images by using two adversarial networks. A GAN architecture is composed of two component parts, including a generation model G and a discriminant model D (Figure 1) [34]. The G model is responsible for producing spurious data whereas the D model is in charge of distinguishing the authenticity of the produced data.…”
Section: Generative Adversarial Network (Gan)mentioning
confidence: 99%
“…For this purpose, deep generative models are utilized to augment the CXR image dataset. Previous studies have demonstrated the generation of CXR images using deep generative models, including generative adversarial networks (GANs) and diffusion models [2,3,5,6,19,21,27,31,43]. CXR images are typically annotated with radiology reports detailing clinical observations made by radiologists, as depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The generated CXR reports exhibit promising performance in terms of both natural language metrics and clinical efficacy metrics. In recent years, Generative Adversarial Networks (GANs) are frequently adopted for generating CXR images, and promising results were attained [2,3,19,21,27,31,39,46]. Nonetheless, GANs exhibit problems including mode collapse and training instabilities, which increase training difficulties, and degrade generation quality.…”
Section: Introductionmentioning
confidence: 99%